\( (\mathrm{g})^{*} \quad \) Prove that \( (1-x)\left(1+x+x^{2}+\ldots+x^{99}\right)=1-x^{100} \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
The Deep Dive
To prove the equation \( (1-x)\left(1+x+x^{2}+\ldots+x^{99}\right)=1-x^{100} \), we start by simplifying the left-hand side. The expression inside the parentheses, \( 1+x+x^{2}+\ldots+x^{99} \), is a geometric series with the first term 1 and the common ratio \( x \). The sum of a finite geometric series can be calculated using the formula: \[ S_n = \frac{a(1 - r^n)}{1 - r} \] where \( a \) is the first term, \( r \) is the common ratio, and \( n \) is the number of terms. In our case, \( a = 1 \), \( r = x \), and \( n = 100 \) (from \( x^0 \) to \( x^{99} \)). Thus, we have: \[ 1+x+x^{2}+\ldots+x^{99} = \frac{1(1 - x^{100})}{1 - x} = \frac{1 - x^{100}}{1 - x} \] Now substituting this sum back into our original expression: \[ (1-x)\left(1+x+x^{2}+\ldots+x^{99}\right) = (1-x)\left(\frac{1 - x^{100}}{1 - x}\right) \] Next, notice that the \( (1-x) \) in the numerator and the denominator cancels out, provided \( x \neq 1 \): \[ = 1 - x^{100} \] Thus, we have shown that: \[ (1-x)\left(1+x+x^{2}+\ldots+x^{99}\right) = 1 - x^{100} \] This completes the proof.